Road side-to-vehicle communications - Saeed, Rashid Abdelhaleem (IIUM Press, 2011)
Wireless vehicular communication (WVC) has been identified as a key technology for intelligent transportation systems (ITS) for the past few years. IEEE 802.1 " 'Iproposed standard for the physical and MAC layer of the WVC devices. The main objective of the standard is to change the frame format in order to increase the delay spread tolerance introduced by the vehicle mobility, in which the channel bandwidth is scaled from 20 MHz. i.e.. 802.11 a to 10 MHz, i.e., 802.11 p. This chapter proposes the TD~·lA technique with fixed time slots and a guard band between the slots to ensure interoperability between the wireless devices to communicate in rapidly changing environment where transactions must be completed in small timcframes. The new TDMA sub-layer is proposed to be on top of the coventional 802.llp CSMA/CA MAC. We have found that 802.11 p-based TDMA can achieve much higher throughput compared with the conventional 802.11 p-based CSMA/CA, as the distance, vehicle speed and numbers increase. Ns-2 simulation results present the performce analysis and validate the efficiency of the proposed scheme